Ground-state lifetime measurements in Tellurium decay chains: Analysis and Results - Efstathiou, Margarita; Koseoglou, Pavlos; Vasileiou, Polytimos; Mertzimekis, Theo J.; Zyriliou, Aikaterini; Karadimas, Angelos; Mihai, Constantin; Marginean, Nicolae Marius; Lica, Razvan; Costache, Cristian; Turturica, Andrei; Mihai, Radu-Emanuel; et al. (HNPS Advances in Nuclear Physics, 2026)
The isotopes of Tellurium are located near the stability line on the isotopic chart, making them important for study in the context of nuclear theory and in terms of applications. In this work, we present a study of the radioactive decay chains of Tellurium isotopes with mass numbers 117 and 115, aiming to investigate their ground-state half-lives as determined from an experiment conducted at the 9 MV Tandem accelerator at IFIN-HH in Romania. Key parts of this presentation are a novel approach used to extract the experimental half-life values, as well as its application to the experimental data obtained for the two Tellurium decay chains. A comparison of the results for the half-lives obtained with and without the application of this approach will also be presented to demonstrate its capabilities. The approach does not rely on any input from the literature, and it allows for a significant reduction in the uncertainties associated with the extracted half-life values, thus enhancing the reliability and precision of the results.